Physical property analysis and preserved relative amplitude processed seismic imaging of volcanogenic massive sulfides-a case study from Neves-Corvo, Portugal - Yavuz, S.; Kinkela, J.; Dzunic, Aleksandar; Penney, M.; Neto, R.; Araújo, V.; Ziramov, Sasha; Pevzner, Roman; Urosevic, Milovan (Blackwell Publishing Ltd, 2015)
Neves–Corvo is one of the biggest mining districts on the Portuguese side of the Iberian Pyrite Belt hosting six different lower Carboniferous copper, zinc, lead and tin orebodies including Lombador, Neves, Graça, Corvo, Zambujal, and Semblana. During the past 50 years, geological, geochemical, and geophysical methods were utilized in the exploration of volcanogenic massive sulfide deposits at Neves–Corvo. Electromagnetic, earth resistivity, and principally gravimetry methods played major roles in the geophysical exploration of the area. However, in 2011, as the exploration depth for volcanogenic massive sulfide mineralization became ever deeper, the surface reflection seismic technique was trialled. Initially, elastic property measurements were employed on numerous core samples to determine the seismic properties of the major formations of Neves–Corvo. The contrast in acoustic impedance values derived from these measurements showed that there should be a significant difference in the seismic response of mineralization relative to the surrounding host rocks. Based on this, a high-resolution 3D seismic survey was acquired over the Neves–Corvo mine and its southeastern extension in order to image known deep volcanogenic massive sulfide mineralization to validate the seismic reflection technique and to potentially identify new mineralization targets. As a result, the Semblana and Lombador deposits were successfully imaged, along with key lithological contacts and geologic structures. Additionally, copper sulfide extensions south of Semblana were discovered. Unfortunately, all of the high-priority targets that were identified from the seismic data were subsequently drilled and many of them found to be non-economic.In order to overcome the non-uniqueness of the original seismic data, full-waveform sonic and pseudo-logs were used to model different interfaces and calibrate the seismic data. These results indicated that preserved relative amplitude processing might be of importance to help reduce the ambiguity in direct detection of volcanogenic massive sulfide based on seismic amplitude anomalies. The customized relative amplitude processing of a sub-dataset over the Semblana deposit was then performed. The newly obtained seismic cube was calibrated with existing drillholes, and a volumetric interpretation was performed by utilizing amplitude-based geobodies. Eventually, superior target zonation and precision for the subsequent deep drilling campaign was achieved with the revised interpretation, clearly showing that the high priority targets originally identified from the legacy data would not have passed the targeting criteria in the reprocessed data due to their relatively weak amplitude response. The results obtained from this study inspired the subsequent reprocessing of the full seismic dataset.